A nanoparticle formulation of disulfiram prolongs corneal residence time of the drug and reduces intraocular pressure. (March 2015) - Nagai, Noriaki; Yoshioka, Chiaki; Mano, Yu; Tnabe, Wataru; Ito, Yoshimasa; Okamoto, Norio; Shimomura, Yoshikazu
Abstract: The goal in the search for successful therapies for glaucoma is the reduction of intraocular pressure (IOP), and the search for effective eye drops that reduce IOP is a high priority. We previously reported the potential of a 2-hydroxypropyl-β-cyclodextrin (HPβCD) solution containing 0.5% DSF (DSF solution) to provide effective anti-glaucoma treatment in eye drop form. In this study, we designed new ophthalmic formulations containing 0.5% DSF nanoparticles prepared by a bead mill method (DSFnano dispersion; particle size 183 ± 92 nm, mean ± S.D.), and compared the IOP-reducing effects of a DSFnano dispersion with those of a DSF solution. The high stability of the DSFnano dispersion was observed until 7 days after preparation, and the DSFnano dispersion showed high antimicrobial activity against Escherichia coli (ATCC 8739). In transcorneal penetration experiments using rabbit corneas, only diethyldithiocarbamate (DDC) was detected in the aqueous humor, while no DSF was detected. The DDC penetration level (area under the curve, AUC ) and corneal residence time (mean residence time, MRT ) of the DSFnano dispersion were approximately 1.45- and 1.44-fold higher than those of the DSF, respectively. Moreover, the IOP-reducing effects of the DSFnano dispersion were significantly greater than those of the DSF solution in rabbits (the IOP was enhanced by placing the rabbits in a dark room for 5 h). In addition, DSFnano dispersion are tolerated better by a corneal epithelial cell than DSF solution and commercially available timolol maleate eye drops. It is possible that dispersions containing DSF nanoparticles will provide new possibilities for the effective treatment of glaucoma, and that an ocular drug delivery system using drug nanoparticles may expand their usage as therapy in the ophthalmologic field. These findings provide significant information that can be used to design further studies aimed at developing anti-glaucoma drugs. Highlights: We designed new eye drops containing disulfiram nanoparticles (DSFnano dispersion). Particle size of DSFnano dispersion is 183 ± 92 nm. DSFnano dispersion showed a high stability for 7 days after preparation. Corneal penetration and residence time of DSFnano dispersion is very high. DSFnano dispersion provides new possibilities for effectively treating glaucoma.